1997
DOI: 10.1093/bja/78.1.95
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desflurane and isoflurane on splanchnic microcirculation during major surgery

Abstract: Isoflurane has been considered the agent of choice where preservation of splanchnic blood flow is required. Liver blood flow and the hepatic artery buffer response are maintained better in the presence of isoflurane than with other volatile anaesthetic agents. The effects of desflurane have not been assessed in humans. Therefore, we have compared the effects of isoflurane and desflurane anaesthesia on small bowel and hepatic microcirculatory flow during major surgery using laser Doppler flowmetry in a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(25 citation statements)
references
References 4 publications
0
24
0
1
Order By: Relevance
“…Volatile anesthetic agents, particularly halothane, have been reported to decrease hepatic blood flow and hepatic clearance rates. However, the inhaled agents in our patients, flurane and isoflurane, are short acting and have a negligible effect on hepatic blood flow and clearance following surgery (8,18,31). Also, clearance rates of sex steroids are actually increased rather than decreased after CABG (51).…”
Section: Discussionmentioning
confidence: 84%
“…Volatile anesthetic agents, particularly halothane, have been reported to decrease hepatic blood flow and hepatic clearance rates. However, the inhaled agents in our patients, flurane and isoflurane, are short acting and have a negligible effect on hepatic blood flow and clearance following surgery (8,18,31). Also, clearance rates of sex steroids are actually increased rather than decreased after CABG (51).…”
Section: Discussionmentioning
confidence: 84%
“…26,27 N-acetylcysteine and antioxidants were infused to confer hepatic protection. 28 The antifibrinolytic drug tranexamic acid was administered to maintain platelet function and prevent fibrinolysis resulting from the "anhepatic phase."…”
Section: Anesthetic Techniquementioning
confidence: 99%
“…Isoflurane, which was used in the case, at concentrations of 1.5 to 2.0 MAC may reduce portal blood flow [14] and it may decrease hepatic oxygen delivery and total HBF by 31% to 37% [15,16]. However, other studies have found an increase in HBF by isoflurane [17] or only minimal overall effect [18]. Fentanyl increases hepatic oxygen uptake by 50% and does not affect hepatic venous blood oxygen content or HBF [15,19].…”
Section: Discussionmentioning
confidence: 99%